2014
DOI: 10.1212/wnl.0000000000000168
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and progression of generalized small-vessel disease

Abstract: Our findings implicate a role for homocysteine in the development of a generalized small-vessel disease in which both brain and kidney are affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 31 publications
(28 reference statements)
2
40
0
1
Order By: Relevance
“…CVD-induced cognitive impairment is primarily associated with microvascular disease, which reduces blood flow to white matter, and has been shown to significantly increase white matter atrophy and ischemic white matter changes in HHcy patients and in cognitively normal adults, 55 years and older, with CVD [19,20]. Cortical atrophy is also linked to microvascular disease.…”
Section: Primary Outcomesmentioning
confidence: 99%
“…CVD-induced cognitive impairment is primarily associated with microvascular disease, which reduces blood flow to white matter, and has been shown to significantly increase white matter atrophy and ischemic white matter changes in HHcy patients and in cognitively normal adults, 55 years and older, with CVD [19,20]. Cortical atrophy is also linked to microvascular disease.…”
Section: Primary Outcomesmentioning
confidence: 99%
“…The association with hippocampal atrophy appears to be independent of amyloid pathology [14]. White matter lesions reflect vascular damage [92] and it is therefore notable that white matter changes are associated with HHCy [47,49,64,94] and with low vitamin B 12 levels [21] and low folate [51,100]. Evidence supporting a causal relationship between HHCy and cerebrovascular injury includes: i) independent, graded association of HHCy with stroke in prospective and retrospective clinical studies [48,61]; ii) genetic association studies of genes regulating HCy metabolism, using Mendelian randomisation [9]; iii) HHCy-induced lesions in experimental animals [4,68,108,111].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperhomocysteinemia is thought to affect the hippocampus more strongly than any other part of the brain. It has been recently reported that hyperhomocysteinemia affects the cerebral smaller vessels more than major vessels [19]. Blood of hippocampal region is supplied via the anterior choroidal artery, which arises from distal to the bifurcation of the posterior communicating artery, and is classified as a perforator branch.…”
Section: Discussionmentioning
confidence: 99%